Encyclopedia of Life Sciences 2019
DOI: 10.1002/9780470015902.a0028403
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Peptides as Potential Therapeutics

Abstract: Stapled peptides are an important class of conformationally constrained, bioactive α‐helical peptides. They have been used extensively as chemical probes for the regulation of protein–protein interactions (PPIs), with one currently progressing through late‐stage clinical trials as a peptide drug candidate. Their ability to interact with shallow protein–protein interfaces, which have previously proven to be challenging to target with small molecules, has led to their rapid uptake by the chemical biology and dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[17,18] They have been shown in numerous biologically relevant examples (e.g., p53/MDM2, Bcl2 and Aurora-A/TPX2) to have excellent binding affinity, selectivity and also favorable DMPK properties. [19] Soluble ACE2 has been investigated as a potential therapeutic, acting as a competitive interceptor of SARS-CoV-2 and preventing viral binding to cells. [20] Recent studies have shown that human recombinant soluble ACE2 (hrsACE2) have shown promise for treating severe COVID-19.…”
Section: Stapled Peptides Have Recently Come Of Age As Tool Compoundsmentioning
confidence: 99%
“…[17,18] They have been shown in numerous biologically relevant examples (e.g., p53/MDM2, Bcl2 and Aurora-A/TPX2) to have excellent binding affinity, selectivity and also favorable DMPK properties. [19] Soluble ACE2 has been investigated as a potential therapeutic, acting as a competitive interceptor of SARS-CoV-2 and preventing viral binding to cells. [20] Recent studies have shown that human recombinant soluble ACE2 (hrsACE2) have shown promise for treating severe COVID-19.…”
Section: Stapled Peptides Have Recently Come Of Age As Tool Compoundsmentioning
confidence: 99%
“…We employed the hydrocarbon‐stapling (HCS) strategy developed by Verdine and co‐workers [ 32 ] as the unnatural amino acids required are commercially available. [ 33 ] The linear peptide 13 incorporating ( R )‐N‐Fmoc‐α‐(7‐octenyl) alanine at position i and ( S )‐N‐Fmoc‐α‐(4‐pentenyl)alanine at position i + 7 was prepared using standard Fmoc/ t Bu SPPS methods. Linear peptide 14 , incorporating two ( S )‐N‐Fmoc‐α‐(4‐pentenyl)alanine residues in the i and i + 4 positions (Scheme 2C) was also prepared to provide the shorter conformational constraint.…”
Section: Resultsmentioning
confidence: 99%
“…We employed the hydrocarbon-stapling (HCS) strategy developed by Verdine and co-workers [32] as the unnatural amino acids required are commercially available. [33] The Furthermore, as RCM of peptide 13 produced both the cis and trans isomers 3 and 4 and to investigate further the effect of the carbon-carbon double bond on the effectiveness of the hydrocarbon constraint, we also produced the reduced i,i + 7 staple 5. After RCM to produce peptides 3 and 4, the double bond was reduced on resin, using triisopropylbenzenesulfonyl hydrazide under basic conditions and elavated temperature to provide saturated stapled peptide 5 (Scheme 2B).…”
Section: Patch-clamp Assaymentioning
confidence: 99%
“…In this regard, peptide-based inhibitors have been significant achievements in targeting and regulating intracellular protein-protein interaction. Stapled peptides are synthetic, bioactive α-helical peptides locked into their bioactive structure that have brought new hope to target drug discovery [135,136]. For instance, stabilized alpha-helix of Bcl-2 domains, SAHBs, is the peptide having the ability to penetrate leukaemia cells and trigger induction of apoptosis through its binding to the Bcl-xL which its function has been further confirmed though invivo mouse xenograft models of leukaemia [137].…”
Section: Therapeutic Opportunities Based On Bcl-2 Family Proteins Modulationmentioning
confidence: 99%